Pengaruh Pengungkapan ESG, Leverage, dan Likuiditas Terhadap Kinerja Keuangan Perusahaan - Albinurrizqi, Duta; Hamzani, Umiaty; Astarani, Juanda (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The ambiguity surrounding the influence of ESG on corporate financial outcomes forms the foundation of this study. This study aims to analyze the role of ESG disclosure, debt ratio, and short-term solvency in determining the financial outcomes of banking institutions in Indonesia. A quantitative descriptive approach was employed, focusing on 42 banking institutions recorded on the Indonesia Stock Exchange during the 2021-2023 period. Using the purposive sampling approach, a total of 54 entities were selected as the research sample. Secondary data were examined through Eviews 12 to verify the proposed hypothesis. The results of the penelitian reveal that ESG transparency has no bearing on financial performance. In contrast, financial metrics tend to rise with increased leverage. This corresponds with the agency theory, suggesting that well-structured debt can contribute positively to financial efficiency. Meanwhile, liquidity has no statistically relevant effect. To enhance performance, it is recommended that the company revisit its ESG strategy and concentrate on optimizing liabilities and short-term assets.